Business and Sustainability with a Social and Environmental Aproach - Hinojosa Pérez, Anatolia Hortencia; Condori Cáceres, Ysela (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
Currently there is a general concern for the efficient use of resources both in companies and in society. Therefore, the present aims to analyze the relationship between business and sustainability with a social, economic and environmental study approach. A review of the literature from reliable sources was carried out, where the importance of sustainability is analysed from a theoretical perspective with business application based on the principles of environmental economics. The present work had as results the importance of the concept of sustainability in organizations from a vision of Environmental Economics and Circular economics.